Metaphysics of Detective Marlowe : Style, Vision, Hard-Boiled Repartee, Thugs, and Death-Dealing Damsels in Raymond Chandler's Novels. - Mihaies, Mircea (Lexington Books, 2013)
Raymond Chandler's role in the reshaping of hard-boiled literature can hardly be exaggerated. He shattered the dogmas of a genre content to be popular, and paved the way for a noble, complex and aristocratic destiny. He implemented his revolutionary vision by radical changes in style, manner, and character construction. Like his hero, Philip Marlowe, he was fascinated with the metaphysical features of existence: honor, pride, loneliness, disenchantemnet, futility, failure, horror, boredom, alienation, rebellion, fear, moral paralysis. In The Metaphysics of Detective Marlowe, Mircea Mihaies reexamines the major contradiction of Chandler's hero: though in the service of truth, he is often forced to realize that truth is sordid, repulsive, malicious, aggressive, and rapacious. Out of this baffling position, a new American genre and type of hero have emerged.